2019
DOI: 10.1038/s41467-019-13166-6
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and durable wood-based triboelectric nanogenerators for self-powered sensing in athletic big data analytics

Abstract: In the new era of internet of things, big data collection and analysis based on widely distributed intelligent sensing technology is particularly important. Here, we report a flexible and durable wood-based triboelectric nanogenerator for self-powered sensing in athletic big data analytics. Based on a simple and effective strategy, natural wood can be converted into a high-performance triboelectric material with excellent mechanical properties, such as 7.5-fold enhancement in strength, superior flexibility, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
257
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 416 publications
(258 citation statements)
references
References 38 publications
0
257
0
1
Order By: Relevance
“…However, a recent study [ 19 ] has indicated that cellulose acetate has a higher triboelectric effect than polytetrafluoroethylene (PTFE). This finding implies the great potential of cellulose‐based materials [ 20 ] for use in environmentally friendly TENGs [ 21 ] with performances close to those using fluoropolymers.…”
Section: Figurementioning
confidence: 95%
“…However, a recent study [ 19 ] has indicated that cellulose acetate has a higher triboelectric effect than polytetrafluoroethylene (PTFE). This finding implies the great potential of cellulose‐based materials [ 20 ] for use in environmentally friendly TENGs [ 21 ] with performances close to those using fluoropolymers.…”
Section: Figurementioning
confidence: 95%
“…[25,27,45,46] The triboelectrification phenomena can occur in almost all types of materials, e.g., polymers, ceramics, and metals, and at different interfaces, e.g., solid-solid, solidliquid, and liquid-liquid. [47][48][49][50][51] The structure of TENG consists of conducting electrodes, [34,[52][53][54] (e.g., metals, conductive gel etc.) and two triboelectric layers that have different electronegativities.…”
Section: Basics Of Triboelectric Nanogeneratorsmentioning
confidence: 99%
“…In order to efficiently collect the wide range of various environmental mechanical energies, such as walking, tapping, sliding etc., four modes of TENGs have been proposed and demonstrated, including lateral sliding mode, [56][57][58][59] vertical contact-separation mode, [45,52,60,61] freestanding mode, [62][63][64] and single-electrode mode. [24,48,50,65,66] Compared with traditional mechanical energy harvesting devices based on mechanisms such as piezoelectric [19,67,68] and electromagnetic effects, [69][70][71] TENG has its advantages regarding the versatile material selection, lightweight, flexibility, low cost, high conversion efficiency, etc. [25,33,34] The electrical outputs can be used to power small electronics (such as an electronic watch, LEDs, calculator, small sensors) [72][73][74][75][76][77] or as the sensing signal in self-powered sensor systems.…”
Section: Basics Of Triboelectric Nanogeneratorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8,14–21 ] Thus, the TENG technology can provide a possible solution for maintenance‐free power supply in IoTs, which can further combine with energy storage devices, such as capacitors, to achieve self‐powered systems. [ 22–27 ] However, although there are lots of attempts in this field, the proposed devices are usually dependent on single energy source, which cannot ensure reliable power supply. Some recently reported hybrid devices have also been attempted to harvest multiple forms of environmental energy, but they are not suitable for working in all‐weather harsh environment, and their output power still needs to be further improved for practical applications.…”
Section: Introductionmentioning
confidence: 99%